Imagination theory: Anthropological perspectives. (June 2023) - Rohrer, Ingo; Thompson, Michelle
The term imagination and its derivatives often serve as points of departures, yet a concise understanding of imagination in anthropology is lacking. In this paper, we argue for a contextualized anthropological approach to imagination; a complex notion which has been used to describe the human capacity to mentally (re)create that what is not materially present; the creative process of imagining; and the individual and social products of such a process. We address terminological particularities, conceptual differences, and related concepts in addition to discussing the importance of methods and the poetic imagination. In doing so, we consolidate and elaborate on previous analytical and conceptual works to provide a more explicit middle-range theory of imagination from an anthropological perspective. While we propose understanding imagination as a guiding action in situations of uncertainty or ignorance and emphasize focusing on everyday processes and practices, our discussions provide a framework to discuss and compare empirically grounded findings regarding imagination.